Associative and perceptual learning and the concept of memory systems - Gaffan, D (1997)
An introductory review is followed by some new experimental data and a final discussion. The primate temporal lobe contains multiple qualitatively distinct memory systems. The functional properties of these memory systems can be explained by reference to the nature of the afferent information which they process, rather than by reference to any putative specialization in memory processing. In this way, the plasticity of 'memory systems' in associative memory is probably similar in principle to the plasticity of 'perceptual systems' in perceptual learning. Therefore, it is important to consider the relationship between perceptual and associative learning. Two experiments investigated perceptual learning in the Rhesus monkey (Macaca mulatta). Substantial perceptual learning was observed both with complex scenes and with simple colours. Two hypotheses as to the basis of perceptual learning are discussed. A physiological hypothesis is that training with a particular set of stimuli expands the cortical representation of those stimuli. This can explain the effects in both experiments. A psychological hypothesis is that perceptual learning is produced by learned associations among the multiple features of complex stimuli. This can explain the effects in Expt. 1 but not in Expt. 2. The psychological associative hypothesis is therefore redundant. Furthermore, associative learning can itself be viewed as an expansion of the cortical representation of a complex event. Thus, the distinction between perceptual and memory systems will need to be abandoned as deeper understanding of cortical plasticity is achieved.